Cancerous lesions in the vicinity of dental implants: a systematic review - Salgado-Peralvo; Serrano-Sánchez Víctor; Vaello-Checa Iris; Helm Alexandra; Mateos-Moreno; Salgado-Velázquez Alberto (EDP Sciences, 2020)
Introduction: The massive diffusion of dental implant treatments in the last decades leads to the appearance of complications, most of them inflammatory, although important complications have been described as malignant lesions in the vicinity of dental implants. The objective of this article is to describe the cases described in the literature of oral squamous cell carcinoma (OSCC) or clinical variants and metastases, in the vicinity of dental implants and to analyze the possible etiological agents involved. Material and methods: The criteria used were those described in the PRISMA® Declaration for performing systematic reviews. An electronic search was performed on MEDLINE (via PubMed) using the terms MeSH: "dental implants" AND "squamous cell carcinoma" OR "dental implant complications" AND "squamous cell carcinoma". Results: Thirty-eight articles describing a total of 76 cases of OSCC or clinical variants, as well as metastasis in the vicinity of dental implants, were included. Conclusions: It is not possible to establish a cause-effect relationship between dental implants and the development of OSCC. Its clinical appearance can be confused with periimplantitis, so that, in cases of sudden onset, which do not respond to conventional treatment and/or have associated alterations in sensitivity, a biopsy should be performed.